2020
DOI: 10.1159/000506517
|View full text |Cite
|
Sign up to set email alerts
|

Direct Current Electric Field Stimulates Nitric Oxide Production and Promotes NO-Dependent Angiogenesis: Involvement of the PI3K/Akt Signaling Pathway

Abstract: Electric fields (EFs) promote angiogenesis in vitro and in vivo. These results indicate the feasibility of the application of EFs to modulate angiogenesis. Nitric oxide (NO) derived from endothelial nitric oxide synthase (eNOS) is an important regulator of angiogenesis. However, the role of direct current EFs in eNOS activity and expression in association with angiogenesis of endothelial cells has not been investigated. In the present study, we stimulated human umbilical vein endothelial cells (HUVECs) with EF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…The application of DC EFs is known to significantly increase the activation of AKT and impact the PI3K/AKT pathway, which plays an important role in cell survival, growth, migration, and metabolism [46]. Further, DC-induced activation of the PI3K/AKT pathway was also reported in different cell types, including neural progenitor cells [47], Schwann cells [48], and human umbilical vein endothelial cells (HUVEC) [49], as well as in ocular cells, including the corneal epithelium [6,50]. Activation of the MAPK signaling pathway is also reported through the application of EFs in neuronal cells [51,52], fibroblasts, HUVEC [53], and corneal epithelial cells [6].…”
Section: Discussionmentioning
confidence: 99%
“…The application of DC EFs is known to significantly increase the activation of AKT and impact the PI3K/AKT pathway, which plays an important role in cell survival, growth, migration, and metabolism [46]. Further, DC-induced activation of the PI3K/AKT pathway was also reported in different cell types, including neural progenitor cells [47], Schwann cells [48], and human umbilical vein endothelial cells (HUVEC) [49], as well as in ocular cells, including the corneal epithelium [6,50]. Activation of the MAPK signaling pathway is also reported through the application of EFs in neuronal cells [51,52], fibroblasts, HUVEC [53], and corneal epithelial cells [6].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, EFs have been identified to regulate pathways involving phosphatase and kinase activity. Numerous reports have confirmed the ability of EFs to induce activation of Akt, and signal transduction of the PI3K pathway ( Arocena et al, 2010 ; Meng et al, 2011 ; Wang et al, 2013 ; Dong et al, 2019 ; Yang et al, 2019 ; Wei et al, 2020 ). Additionally, multiple studies have identified various electrical field parameters to increase production of nitric oxide (NO) both in vivo and in vitro ( Petrofsky et al, 2007 ; Kim et al, 2013 ; Trivedi et al, 2013 ; Wei et al, 2020 ).…”
Section: Future Workmentioning
confidence: 91%
“…Bioelectric signals are reported to influence angiogenesis, the formation of blood vessels within existing vasculature. Electric field-induced angiogenesis has been identified in endothelial cells receiving electrical stimulation ( Wei et al, 2020 ). Blood flow increases in response to electrical fields, and blood flow alone causes a change in electric field potential ( Petrofsky et al, 2007 ; Trivedi et al, 2013 ).…”
Section: Enhancing Organoid Cultures With Bioelectricitymentioning
confidence: 99%
“…Angiogenesis is maintained by the overproduction of proangiogenic factors, including growth factors, matrix proteinases, and extracellular matrix molecules [100,102]. Different approaches have already shown that eNOS-derived NO signaling in endothelial cells is a critical mechanism of vascular homeostasis, mediating angiogenesis and contributing to increased cell proliferation and migration of endothelial cells and consequently to tumor progression [103][104][105]. Since eNOS activity requires BH4 as a cofactor for NO production, it was shown that the maintenance of its bioavailability is essential for angiogenesis by many groups using different technical procedures [60,61,106,107].…”
Section: Tumor Microenvironment and Angiogenesismentioning
confidence: 99%